Video Technology: A Much Needed Resource in Nigerian Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Video is technology that involves the recording and playback of moving pictures and sound. It is any electronic medium that is used to record, copy, playback, broadcast and display moving visuals. It has revolutionalised education in recent times. This is because education is no longer restricted to the four walls of a classroom as people can learn anywhere, anytime and in any situation. This work has focused on the proliferation of video technology and the reasons it is and should be embraced in the Nigerian educational system. Some of the reasons are the recuring global health issues like COVID, Ebola and bird flu which shouts down towns and nations; seasonal floods, insecurity; a favourable ICT in Education policy, and so on. It also discussed the challenges facing its use as a medium of instruction. Some of the challenges are non-implementation of government policies by state and local governments who have the responsibility; shortage of digital infrastructure and skills; ignorance, and technophobia; lack of motivation, and so on. Some solutions have been identified as to how a lot of the challenges can be overcome. Video technology is a huge industry. The country stands to gain massively if it is effectively used in the educational system.